Experimental study on surface reaction during water injection on molten Zr/Fe pool. (June 2022) - Liu, Ren; Han, Kun; Chen, Lian; Fang, Fang-fang; Li, Zongyang; Zhang, Yaoli; Hong, Gang
Highlights: Neither vapor explosion nor melt ejection is found for the investigated experimental conditions. When the content of Zr is 60%, H2 produced by Zirconium-water reaction accounted for a small proportion of total gas generation but led to some cavities on the metal production. There were three kinds of oxides on the surface of metal production all of which composed of oxides of iron and zirconium in different proportions. Abstract: In the postulated severe nuclear accident which caused core degradation, water injection can introduce coolant to cool the molten pool and enhance the effectiveness of In-Vessel Retention (IVR) strategy. However, the existing research did not use the prototypical materials, so the effect of Zirconium-Water reaction (ZWR) was not taken into account. In this study, the wATater injectiOn on molten Zirconium-stainless steel Metallic pool experiment (ATOM) has been established to verify the effect of ZWR during water injection. Neither vapor explosion nor melt ejection found during all tests. The production of hydrogen accounts for only about 1/1000 of total amount of vapor, and the maximum pressure increment is 1.0 kPa. These results show that the existence of Zirconium-water reaction will not damage the safety of water injection strategy, and strongly support the feasibility of water injection strategy in severe nuclear accident. The result also showed that when the content of zirconium is 60%, the H2 produced by ZWR can be measured. Hydrogen produced in water injection accounted for a small proportion of gas generation, but led to some cavities on the metal production. At the same time, it was found that there were three kinds of oxides on the surface of metal production all of which composed of oxides of iron and zirconium in different proportions.